A Multicriteria Decision Model Based on Analytic Hierarchy Process for Managing Safety in Coal Mines. (4th April 2022) - Wang, Xin; Zhang, Lei
Abstract : This paper presents a comprehensive quantitative approach for managing safety in coal mines with a multicriteria decision-making model by using fuzzy mathematics. We develop a set of factors that affect the management of safety in coal mines, including ventilation, the mine roof, and mine temperature. The factors also include mine dust, mining gas, and mining water. Other factors are equipment reliability, explosive risk of equipment, maintenance of equipment, staff operations and staff training, staff attendance, index to evaluate and manage workload, and project quality, monitoring systems, and safety information. The approach is then applied to evaluate a case study on the safety management of the Fushan Coal Industry Co., Ltd. Coal Mine in Henan Province of China. The matrix that evaluates each factor is obtained through a membership function and scored by experts, and the weight of each attribute is obtained through an analytic hierarchy process. The evaluation results show that the Fushan Coal Industry Co., Ltd. Coal Mine overall has a good safety track record. However, the mine needs to further enhance how they manage safety, optimize the mine ventilation system, and further strengthen safety management practices to ensure the safety of production processes in the mine.